Formative Events, Networked Spaces, And The Political Socialization Of Youth - Kligler-Vilenchik, Neta; Literat, Ioana (AoIR Selected Papers of Internet Research, 2017)
Much academic and public attention is devoted to the question of youth engagement in public life. Over the past decade, concerns about a decrease in youth civic engagement have given way to an examination of new ways in which young people relate to the political realm, often in digitally mediated ways. Youth—as a period of time in life—is of particular consequence to political socialization, as the formative experiences of youth and engagement in politics during this time period shape future patterns of participation and engagement. This article examines how youth responded to the results of the 2016 US elections, as a potential formative political event, in a variety of online networked spaces. Our focus is on what their participation in these spaces reveals in terms of their relationships to traditional politics. We find that these platforms afford youth different modes of expression (including memes, games and artwork) and enable them to communicate openly about politics with peers. At the same time, the discourse on these sites may also exacerbate political cynicism, fear and a disconnection from the political process.